A Chronological Overview of Complete and Partial Translations of the Bible Published in Croatian - Stanko Jambrek; Ruben Knežević (Kairos (English Ed.))
This chronological overview was prepared according to an overview by Ruben Knežević entitled “Bible, Translations, A Chronological Overview of Complete and Partial Translations of the Bible Published in Croatian” published in Leksikon evanđeoskog kršćanstva, [Dictionary of Evangelical Christianity], (Zagreb, Bogoslovni institut and Prometej, 2007). Not included in this overview are: lectionaries, translations of individual Bible books, selected Psalms published in Kajkavian and Chakavian dialects; free literary translations and poetic renderings of the Psalms, as well as those that were published in magazines; individual translations of apocryphal (deutero canonical) books; working, preliminary and exegetical translations in academic journals, handbooks and photocopied course materials; Bible translations of Croatian minorities abroad.